Monitoring indicators of economic activity in Sudan amidst ongoing conflict using satellite data - Abushama, Hala; Guo, Zhe; Siddig, Khalid; Kirui, Oliver K.; Abay, Kibrom A.; You, Liangzhi (International Food Policy Research Institute, 2023)
The confrontation in Sudan between the Sudanese Armed Forces (SAF) and Rapid Support Forces (RSF) had persisted for months before escalating into an armed conflict on April 15th, 2023. Besides the severe humanitarian catastrophe, the war has disrupted access to power, water, health services, and banking services while also disrupting access to markets triggering considerable scarcity of goods and services. The conflict has destroyed key infrastructure, constraining domestic and international trade and disrupting production activities and supply chains. In this paper, we utilize satellite data to provide a swift analysis of how the conflict has changed patterns of economic activity, which are bound to have severe implications on food security in Sudan. We also describe how remote sensing and data collection methods can be deployed to monitor economic activities amidst armed conflicts.